Relationship between Sleep Quality and Quality of Life in Patients with Multiple Sclerosis - Sarraf, Payam (Int J Prev Med, 2014)
BACKGROUND: Impaired quality of life (QOL) is an issue considered in patients with multiple sclerosis (MS). There are limited studies evaluated poor sleep and impaired QOL in these cases. The aim of this study was to evaluate quality of sleep and poor sleep in Iranian patients with MS and the relationship between Pittsburgh Sleep Quality Index (PSQI) score and QOL subscales. METHODS: One-hundred and fourteen cases with definite MS due to MC Donald criteria enrolled who referred to MS clinic of Sina and Imam Hospitals were enrolled. Patients asked to fill valid and reliable Persian versions of PSQI and MSQOL-54 questionnaires. Demographic data (sex, age), duration of the disease, education level and marital status were extracted from patients medical files. After neurological examination, Kurtzke Expanded Disability Status Scale (EDSS) was assessed. RESULTS: Ninety-one (79.8%) patients were female and 23 (20.2%) were male. Mean age and EDSS was 34.7 ± 9.6 years and 2.3 (median: 1.5). Mean PSQI score and overall QOL score were 4.5 and 57. Sixty-seven cases were good sleepers (PSQI ≤ 5) and 47 were poor sleepers (PSQI > 5). Except five subscales, all others were significantly different between good and poor sleepers. There was significant positive correlation between PSQI score and EDSS (r = 0.24, P < 0.001) and negative correlation between EDSS and physical and mental health (r = −0.48, P < 0.001, r = −0.43, P < 0.001). EDSS and total PSQI score were independent predictors of physical and mental health composites. CONCLUSIONS: Sleep quality as a factor which affecting QOL should be considered and evaluated properly in MS patients.